Motivational quotes on entrepreneurship from prophetic hadiths - Mohd Marzuki, Zunaidah (2022)
The Prophet (ﷺ) had set us exemplary as a good and wise businessman both in action and word before and after his prophethood. His focus on da'wah and leadership mission, after his prophethood, includes guiding people on business ruling and ethics based on Allah's revelation which are preserved in many books of Hadith.